The Effect of Snowball Throwing Type Cooperative Learning Model on Learning Outcomes of Grade VIII Students in Subjects of Social Studies at SMP Swasta Parulian 2 Medan - Gultom, Irma; Margareta, Elisabeth; Manullang, Dapot Tua (Jurnal Riset Ilmu Pendidikan, 2025)
This study aims to determine the effect of the Snowball Throwing type of cooperative learning model on the learning outcomes of eighth-grade students in Social Studies at SMP Swasta Parulian 2 Medan. The research employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The sample consisted of two classes: class VIII-2 as the experimental group and class VIII-1 as the control group, totaling 50 students. Instruments used included pretest and posttest questions, observation sheets, and lesson plans (RPP). The results showed that the average posttest scores of students in the experimental class were significantly higher than those in the control class. The hypothesis test using a t-test revealed that the t-value (7.590) exceeded the critical value (1.667), with a significance level (Sig. 2-tailed) of 0.000 < 0.05. Therefore, it can be concluded that the application of the Snowball Throwing cooperative learning model has a significant effect on students’ learning outcomes. This model proved effective in enhancing student engagement, critical thinking skills, and overall academic performance. Hence, the Snowball Throwing model is recommended as an active learning alternative to improve learning achievements in secondary schools.